Culture of Education and Gender Relation: A study on goals of education for women in Sasak, Samawa and Mbojo tribes in Nusa Tenggara Barat - Nurhilaliati Nurhilaliati; Muhammad Muhammad (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to discuss the main issue of education for women in Sasak, Samawa and Mbojo ethnic families. The academic problem based on idea of this research is the persistence of gender-based inequality that is suspected to originate from cultural practices and misconception religious understanding of women-male relations. These two social entities then influence the pattern of education transferred in a family that can shape gender perspectives and relations. The results showed that the purpose of education for women in the three tribes has similarities, namely to produce ideal women according to their respective local wisdom perspectives, namely women who obey customs, have a knowledge, skills, and economic independence.